Proses Material dalam Klausa Bahasa Inggris Pada Teks Asuransi Jiwa: Pendekatan Tata Bahasa Fungsional - Ponia Mega Septiana; Eva Tuckyta Sari Sujatna; Rosaria Mita Amalia (Badan Pengembangan dan Pembinaan Bahasa, 2019)
This research focuses on the material processes that are applied in the text of Life Insurance. The data is obtained from the brochures of Life Insurance in several companies. The collected data are taken randomly. This research discusses two main points: 1) the lexical verb describes the type of material process, and 2) the role of participants are used in the material process within the text. They are analyzed based on the theory of systemic functional linguistic focus on transitivity (material process) by Halliday (2014). This research applies the descriptive qualitative method that uses two techniques. First, selects and collects the clauses. Second, analyze and describes the clause based on the research questions. The result of the research reveals that the lexical verb describes the type of material processes in the text of life insurance. The verbs are an offer, receive, protect, provide, customize, request, access, earn, allow, decrease, increase, lock, change, add, choose, take, pay, buy, build, work, help, and give. Then, the roles of participants are involved in the text such as actor, goal, and recipient. ABSTRAKPenelitian ini merupakan penerapan proses material dalam teks tentang asuransi jiwa. Data dari penelitian ini diperoleh dari brosur – brosur asuransi jiwa dari berbagai perusahaan asuransi. Pengumpulan data diambil secara acak. Penelitian ini membahas dua poin utama yaitu 1) verba leksikal yang menggambarkan tipe material proses. 2) peran partisipant yang digunakan dalam material proses dalam teks tersebut. Teks dianalisis berdasarkan teori Systemic Fuctional Linguistik yang berfokus pada transitivity (material process) dari Halliday (2014). Penelitian ini juga menerapkan metode kualitatif deskripitf dengan menggunakan dua teknik analisis. Pertama, memilah dan mengumpulkan data klausa, dan yang kedua menganalisis dan menggambarkan klausa berdasarkan pertanyaan. Hasil dari penelitian ini mengungkapkan bahwa verba leksikal yang menggambarkan tipe material proses dalam teks asuransi jiwa adalah offer, receive, protect, provide, customize, request, access, earn, allow, decrease, increase, lock, change, add, choose, take, pay, buy, build, work, help, dan give. Selanjutnya, peran partisipant yang terlibat dalam teks seperti actor, goal dan recipient.